1994
DOI: 10.1007/bf00798123
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics and pharmacokinetics of esmolol, a short-acting β-blocking agent, in children

Abstract: Esmolol, a short-acting intravenous cardioselective beta-blocking agent, was evaluated for age-dependent pharmacodynamic and pharmacokinetic features in 17 young patients (6 months to 14 years). A loading dose (500 micrograms/kg/min) alternating with a maintenance dose (25-200 micrograms/kg/min, titrating by 25 micrograms/kg/min every 4 min) was infused until the heart rate or mean arterial pressure decreased 10%. Cardiac index, left ventricular shortening fraction, and systemic vascular resistance were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…As anticipated, the LOQ with this LC-MS was lower than assays that utilized UV detection methods [3,4,6,7], or gas chromatography methods [8]. Most importantly, the sample volume required for this assay was significantly smaller than all previously reported methods, and will allow for multiple sampling in infants and children.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…As anticipated, the LOQ with this LC-MS was lower than assays that utilized UV detection methods [3,4,6,7], or gas chromatography methods [8]. Most importantly, the sample volume required for this assay was significantly smaller than all previously reported methods, and will allow for multiple sampling in infants and children.…”
Section: Discussionmentioning
confidence: 96%
“…Quon and Stamfli initially reported that NaF was an effective inhibitor of esmolol esterase [2]. Numerous other investigators then used NaF as an inhibitor when studying the pharmacokinetics of esmolol [3,4,[9][10][11]. In 1991 Fan and Zhao reported that NaF concentrations as high as 30 mg/ml were unable to inhibit ex vivo metabolism, but detailed data were not presented [6].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…supraventricular tachycardia) and hypertension control after repair of coarctation. [42][43][44][45][46][47][48] Wiest and colleagues [48] utilized esmolol for acute postoperative hypertension in an open-label trial of pediatric patients after cardiac surgery. They included 20 cardiac surgery patients (10 with aortic coarctation repair, 10 with other congenital heart defect repairs) aged 1 month-12 years.…”
Section: Esmololmentioning
confidence: 98%
“…They should not be used in patients with obstructive lung disease, such as asthma, and should be used with caution if the patient has congestive heart failure. Published experience on labetolol and esmolol therapy in pediatrics is limited [39,40].…”
Section: Preferred Antihypertensive Agentsmentioning
confidence: 99%